2019
DOI: 10.1111/cns.13141
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation on mitochondria: Integration of cell and organelle responses

Abstract: Mitochondria are highly integrated organelles that are crucial to cell adaptation and mitigating adverse physiology. Recent studies demonstrate that fundamental signal transduction pathways incorporate mitochondrial substrates into their biological programs. Reversible phosphorylation is emerging as a useful mechanism to modulate mitochondrial function in accordance with cellular changes. Critical serine/threonine protein kinases, such as the c‐Jun N‐terminal kinase (JNK), protein kinase A (PKA), PTEN‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 263 publications
(621 reference statements)
2
34
0
Order By: Relevance
“…Among different types of PTMs (such as phosphorylation, acetylation, succinylation, or SUMOylation), the reversible protein phosphorylation by protein kinases plays an important and not yet fully deciphered role in regulating the mitochondrial metabolism in different physiological and stress states (Stram and Payne, 2016). PTM by protein kinases provides a rapid, reversible, and energetically inexpensive mechanism to regulate the enzyme activity (Lim et al, 2016;Lucero et al, 2019). Among the mitochondrial protein kinases, serine/threonine protein kinase A (PKA) and protein kinase C (PKC) are recognized as crucial regulators of mitochondrial physiology (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different types of PTMs (such as phosphorylation, acetylation, succinylation, or SUMOylation), the reversible protein phosphorylation by protein kinases plays an important and not yet fully deciphered role in regulating the mitochondrial metabolism in different physiological and stress states (Stram and Payne, 2016). PTM by protein kinases provides a rapid, reversible, and energetically inexpensive mechanism to regulate the enzyme activity (Lim et al, 2016;Lucero et al, 2019). Among the mitochondrial protein kinases, serine/threonine protein kinase A (PKA) and protein kinase C (PKC) are recognized as crucial regulators of mitochondrial physiology (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial Complexes I and IV are common substrates for the PKAand PKC-mediated reversible phosphorylation during different physiological and pathological states, including exposure to H/R stress (Ogbi and Johnson, 2006;Prabu et al, 2006;Dagda and Das Banerjee, 2015;Mathers and Staples, 2019). Phosphorylation of Complex I can activate or suppress its activity depending on the species, tissue, and phosphorylation site (Lucero et al, 2019;Mathers and Staples, 2019). Complex IV is typically suppressed by phosphorylation in mammals, and this suppression plays an important role in hypoxiainduced mitochondrial dysfunction (Acin-Perez et al, 2009;Hüttemann et al, 2012;Srinivasan et al, 2013;Mahapatra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PPARGC1A), or PGC‐1a, regulates mitochondrial biogenesis and suppresses oxidative stress . Accumulation of misfolded proteins has been shown to influence neuronal survival and vulnerability in PD . It is also reported that PGC‐1a plays a protective role against 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) toxicity, which has been shown to be a causative factor of PD .…”
Section: Discussionmentioning
confidence: 94%
“…25 Accumulation of misfolded proteins has been shown to influence neuronal survival and vulnerability in PD. 26 It is also reported that PGC-1a plays a protective role against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) toxicity, which has been shown to be a causative factor of PD. 27,28 Rs17590046 in PPARGC1A was found to be significantly associated with increased risk of ET through a GWAS in an European population.…”
Section: Ta B L E 1 Demographic Characteristicsmentioning
confidence: 99%
“…AKAP1/PKA protects against cerebral ischemic stroke by inhibiting Drp1‐dependent mitochondrial fission . Maribel Lucero, Ana E. Suarez, and Jeremy W. Chambers at Florida International University summarized the effects of kinases, phosphatases, and the associated adaptor proteins and scaffold proteins on the OMM in neurons . The authors reviewed the roles of specific substrate phosphorylation or dephosphorylation events including the impacts on mitochondrial dynamics, cell death, fission/fusion, and metabolism.…”
mentioning
confidence: 99%